2009
DOI: 10.1128/aac.01552-08
|View full text |Cite
|
Sign up to set email alerts
|

Sitafloxacin Activity against Helicobacter pylori Isolates, Including Those with gyrA Mutations

Abstract: Sitafloxacin showed MICs of less than or equal to 0.5 g/ml against 105 isolates of Helicobacter pylori, including 44 isolates with mutations in the gyrA gene. The highest MICs for garenoxacin and levofloxacin were 8 and 64 times, respectively, higher than the highest MICs observed for sitafloxacin.The guidelines for the management and treatment of Helicobacter pylori infections established by the European Helicobacter Study Group Third Masstricht Consensus Report recommend an eradication antimicrobial chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 12 publications
4
49
0
Order By: Relevance
“…However, it has been reported that the prevalence of LVX-resistant H. pylori is increasing in several regions and countries [4,5,8,12,13]. In Japan, Matsumoto et al [14] reported that the resistance of H. pylori strains to LVX was 14.2% in cases of CLR-based treatment failure in 2005, but we and others [11] recently found that almost 40% of strains in eradication-naive patients showed LVX MICs of ≥2.0 g/mL, indicating that LVX-resistant H. pylori is increasing. Thus, LVX-based triple therapy might be less effective in our study population as well as in regions with a high prevalence of LVX-resistant H. pylori.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, it has been reported that the prevalence of LVX-resistant H. pylori is increasing in several regions and countries [4,5,8,12,13]. In Japan, Matsumoto et al [14] reported that the resistance of H. pylori strains to LVX was 14.2% in cases of CLR-based treatment failure in 2005, but we and others [11] recently found that almost 40% of strains in eradication-naive patients showed LVX MICs of ≥2.0 g/mL, indicating that LVX-resistant H. pylori is increasing. Thus, LVX-based triple therapy might be less effective in our study population as well as in regions with a high prevalence of LVX-resistant H. pylori.…”
Section: Discussionmentioning
confidence: 77%
“…All rights reserved. doi:10.1016/j.ijantimicag.2011.12.002 mutations [10,11]. In this study, the susceptibility of clinical isolates of H. pylori to STX was evaluated and the efficacy of STX-based triple therapy as a third-line H. pylori eradication regimen was examined.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 60.0% of the patients were infected with levofloxacin-resistant strains of H. pylori. However, sitafloxacin is reported to have a lower MIC than levofloxacin and to be effective in patients infected with strains with mutations in gyrA, a genetic marker for resistance to levofloxacin (8,14). Therefore, in the present study, we used sitafloxacin in patients allergic to penicillin derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, sitafloxacin, a fluoroquinolone, has become clinically available in Japan and is reported to have a lower minimum inhibitory concentration (MIC) for H. pylori (8). Researchers have used sitafloxacin in patients allergic to penicillin with metronidazole and a PPI since 2008 and reported excellent eradication rates.…”
Section: Introductionmentioning
confidence: 99%
“…66 Beside levofloxacin, moxifloxacin has also been used successfully, 67 but it is now recommended to limit the use of this drug in several countries due to various adverse events. There are promising data from Japan especially with sitafloxacin, a fluoroquinolone with higher efficacy especially in case of resistance associated mutations 68 and active at acidic pH. In a large multicenter trial in Japan, in patients receiving a third-line therapy in antibiotic in areas of known high resistance.…”
Section: Ppi-amoxicillin-levofloxacin For 10 Dmentioning
confidence: 99%